Studying The Relationship Between Foreign Trade And GDP Using The Directed Error Correction Model (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to apply the method of directed  error correction model to study the relationship between foreign trade and GDP in Syria. And to find out whether there is a short – and long term equilibrium relationship between these variables.The most important results of the study: there are a short- and long term equilibrium relationship between exports and imports on the one hand and GDP in the other hand. That is a foreign trade explains in the long run 38% of change in GDP.The value of the directed error correction coefficient indicates that the value of foreign trade adjusts towards its equilibrium value in each time period with a percentage of the remaining imbalance from the previous time period  of the previous year equal to 38%.